Sexual Harassment Towards Young People Who Deal With the Public in the Province of Quebec (Journal of Organizational Psychology, 2020)
Several young Canadians have jobs that involve interaction with customers, placing them at risk for public-initiated sexual harassment. To date, research on sexual harassment has focused on outcomes of insider-initiated sexual harassment neglecting public-initiated harassment. Research on the former has shown that sexual harassment has negative outcomes for victims. In this study, I examined the relationship between public-initiated sexual harassment and mental health, physical health, and job satisfaction using hierarchical multiple regression. Participants were female, full-time university students. Results showed that sexual harassment initiated by members of the public was negatively related to employee mental health and physical well-being.
Keywords: Organizational Psychology; young people; public-initiated harassment; sexual harassment; mental health